2023
DOI: 10.3389/fmed.2023.1212321
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculation-guided resuscitation in sepsis: the next frontier?

Abstract: Microcirculatory dysfunction plays a key role in the pathogenesis of tissue dysoxia and organ failure in sepsis. Sublingual videomicroscopy techniques enable the real-time non-invasive assessment of microvascular blood flow. Alterations in sublingual microvascular perfusion were detected during sepsis and are associated with poor outcome. More importantly, sublingual videomicroscopy allowed to explore the effects of commonly applied resuscitative treatments in septic shock, such as fluids, vasopressors and ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…“Resuscitating” the microcirculation is a target of therapy for those patients, but unfortunately few options are currently available to normalize microvascular flow [ 31 ]. Given the high heterogeneity of sepsis a personalized approach is needed and based on the results of this study we encourage further investigation about the effects of ACT on the microcirculation and tissue perfusion of septic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…“Resuscitating” the microcirculation is a target of therapy for those patients, but unfortunately few options are currently available to normalize microvascular flow [ 31 ]. Given the high heterogeneity of sepsis a personalized approach is needed and based on the results of this study we encourage further investigation about the effects of ACT on the microcirculation and tissue perfusion of septic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Independently from cell-free Hb levels, a potential role of the vasculature as a target of the anti-inflammatory effects of ACT has been evaluated in the cerebral microcirculation, where it was demonstrated that ACT protects cultured brain endothelial cells from oxidative stress and oxidative-induced cell death and regulates/reduces cytokine and chemokines secretion from cultured brain [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we integrated microcirculation and mitochondria into a concept called the "critical unit", which we propose is the key link in the occurrence and development of critical illness. On the basis of this understanding, the treatment of critical illness has gradually stepped onto the stage of microcirculation-guided resuscitation and even mitochondria-guided resuscitation; that is, we have arrived at the era of critical unit-guided treatment [3].…”
Section: Introductionmentioning
confidence: 99%